2016
DOI: 10.2147/dddt.s119122
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling methods to analyze the impacts of multiunit process variability on critical quality attributes of Chinese herbal medicine tablets

Abstract: The quality of Chinese herbal medicine tablets suffers from batch-to-batch variability due to a lack of manufacturing process understanding. In this paper, the Panax notoginseng saponins (PNS) immediate release tablet was taken as the research subject. By defining the dissolution of five active pharmaceutical ingredients and the tablet tensile strength as critical quality attributes (CQAs), influences of both the manipulated process parameters introduced by an orthogonal experiment design and the intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It could be concluded that the block of chemical components ( X 2 ) possessed a greater importance than that of colors ( × 1 ) in terms of their correlation with the efficacy of CTP. Likewise, as shown in Figure 5b, the variables involved in each data block were analyzed to determine their importance for the model prediction (Sun et al, 2016). The results revealed the following variables as the ones highly correlating with the hemostatic effect of CTP—a*( x 2 ), 3,4‐dihydroxybenzoic acid ( x 4 ), 4‐hydroxybenzoic acid ( x 5 ), 3‐hydroxybenzoic acid ( x 7 ), quercetin‐3‐ O ‐glucoside ( x 15 ), azelaic acid ( x 16 ), kaempferol‐3‐ O ‐glucoside ( x 18 ), quercetin ( x 19 ), naringenin ( x 20 ), kaempferol ( x 21 ), and isorhamnetin ( x 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…It could be concluded that the block of chemical components ( X 2 ) possessed a greater importance than that of colors ( × 1 ) in terms of their correlation with the efficacy of CTP. Likewise, as shown in Figure 5b, the variables involved in each data block were analyzed to determine their importance for the model prediction (Sun et al, 2016). The results revealed the following variables as the ones highly correlating with the hemostatic effect of CTP—a*( x 2 ), 3,4‐dihydroxybenzoic acid ( x 4 ), 4‐hydroxybenzoic acid ( x 5 ), 3‐hydroxybenzoic acid ( x 7 ), quercetin‐3‐ O ‐glucoside ( x 15 ), azelaic acid ( x 16 ), kaempferol‐3‐ O ‐glucoside ( x 18 ), quercetin ( x 19 ), naringenin ( x 20 ), kaempferol ( x 21 ), and isorhamnetin ( x 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…These plant extracts are very sticky and actually hinder the granulation process. Hence, to improve this unsatisfactory condition, a binder solution such as ethanol is needed to mitigate the extra viscosity [51]. Thus, in this study, ethanol of different concentrations was selected as the binder solution.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of the parameters in the system model can help to identify correlations among the variables of different blocks. Loadings of the model indicate which process parameters and attributes affect product quality and estimate their contribution to quality [45]. The variable importance in the projection (VIP) [46] helps identify the CPPs that contribute most to the product quality.…”
Section: Methodsmentioning
confidence: 99%